KALIMAT TANYA DALAM BAHASA INDONESIA - Pandean, Mariam L.M. (Kajian Linguistik, 2018)
Interrogative sentence is one kind of sentences in Indonesian, which formed as proposition that required answer from hearer. It also called as requesting question. The difference will be recognized from sentence classification perspective. In defining interrogative sentence, syntax, semantics, and pragmatics can be used as the classification tool (Leech, 1981). From syntactic point of view, there are two kinds of interrogative sentence; 1) informative interrogative sentence and 2) confirmative interrogative sentence. Informative interrogative sentence has information request toward one of the element the proposition maker. In this context, proposition maker element can fill one of the syntactic function slot in sentence as function of predicate, object, and complement. But confirmative interrogative sentence requires for distinction of a proposition. Practically, the form is yes or no question. Syntactically, interrogative in Indonesian can be recognized from the question word used. There are many varieties of this type. However, only two elements serve as the basis of interrogative sentence; they are what and where. The derivation of the word apa are who, why, when, how much or how many, and if; the derivation of the word mana are where, where to, from where, how, and when. Semantically, interrogative sentence can be identified from its semantic role of the word that filled the syntactic slot; they are function of predicate, object and complement. In subject function, interrogative sentence can explain the meaning of a deed, time, agent, amount, existence and identity. In object function, it can explain meaning of the target, object, and tool. In semantic role, it can explain the meaning of place, time, member, tool, meaning, cause and target.Keyword: Interrogative sentence, Indonesian language, kind of interrogative sentence